Design and codification of a computer test that measures basketball players’ motor response time and attention focus at the primary level (Journal of Humanities and Social Sciences Research, 2023)
Basketball is a popular sport across the world, as well as in the Arab world and nationally. This is due to its privileged position among sports worldwide, particularly following the rapid and significant development of assistive devices and modern technology used in development processes, as well as the contribution of recent studies and research to reveal the most important psychological factors affecting basketball players. Attention, focus, motor reaction, and other abilities associated with player skills, such as scoring accuracy, are instances of mental processes. Assessing such processes need contemporary testing, such as computers, which are distinguished by their precision in providing results and displaying the player’s true score. As a result, research into establishing automated exams to evaluate them scientifically is critical. For example, measuring basketball players’ motor response time and attention precision. The research question results from the fact that it is one of the issues that experts and trainers acknowledge during the training procedure. It is the method of measuring mental talents and assigning numerical values that are based on contemporary and accurate scientific foundations. This enables professionals to use them in practice, and we additionally lack accurate, objective examinations that depend on technological gear to measure them. Furthermore, if such evaluations exist, they lack criteria by which the coach may appraise the player’s current state. The objective of this research is to construct and design a computer test to measure basketball players’ motor response time and concentration of attention. Furthermore, it finds computerized exam requirements, results, and levels. The human field was represented by basketball players in the Baghdad Governorate, Al-Dhafar Elementary School, the sixth primary school and a temporal field was chosen for the academic season (2022-2023) in this study, while a spatial field was determined for the school’s sports hall and yards. The researcher employed a descriptive strategy, and the research sample was included (46). The researcher reached the conclusion that she had created a computer system that measured motor reaction time and focused attention on basketball players. This occurred at the sixth primary stage. Furthermore, search the standards, grades, and levels for these assessments.